Pemahaman Konselor Sekolah tentang Tugas Perkembangan Siswa dan Layanan yang Diberikan - Hadi, M Fahli Zatra; Yusuf, A. Muri; Syahniar, Syahniar (Universitas Negeri Padang, 2013)
The Guidance and counseling service aims to enable students to realize himself as a person independent, responsible, creative students and productive workers. This study aims to clarify understanding counselor about the developmental tasks of students with a service that is based on the developmental tasks of students, research methods including quantitative descriptive with explaining what the circumstances are. The results of the analysis of the developmental tasks of understanding counselor SMAN Pekanbaru showed that overall results of the analysis showed that the overall average school counselors understand the duties and responsibilities as a school counselor to provide services based on their students' progress.